REVITALISASI KAWASAN CITRA NIAGA SAMARINDA - Gazali, Irsan (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, Kupang, 2017)
Title: Revitalization of Citra Niaga Samarinda Arena promotions and shopping centers nowadays called Citra Niaga as an icon of the capital of Samarinda, which was built in 1984. The design of Citra Niaga is directed to the concept of